PENGARUH BRAND AWARENESS, BRAND ASSOCIATION, BRAND EXTENSION, DAN PERCEIVED QUALITY TERHADAP COSTUMER SATISFACTION (PEMASANG IKLAN) MELALUI BRAND PREFERENCE SINDO MEDIA (MNC GROUP) - Novrianda, Dytta; Maksum, Choril; Moch Jasin (SEKOLAH PASCASARJANA PRESS, 2018)
This research aimed to determine of causal brand awareness, brand association, brand extension,perceived quality to customer satisfaction through brand preference Sindo Media (MNC Group). The type of research is quantity research. The population of research is advertiser, the sample was taken purposive sampling. The sample are collected from advertiser in goverment category (Ministy, Local Government and BUMN), the number of sample was 120 people. The data analysis technique used the SEM (Structural Equation Model). The result showed : Brand awareness, brand assosiate, brand extension, perceived quality has a significant effect on customer satisfaction. Brand awareness, brand association, brand extension and perceived quality was high and will be impact for brand preference. Brand preference of Sindo Media was high, it was customer satisfaction of advertise will be increase. This research showed that brand extension has direct influence to customer satisfaction (31%), it was higher than other variable independent. These assumption, brand extension contribute (0.9%) to brand preference is less than other variabel independent. Brand extensions built inconsistently and confusing advertisers will impact upon the brand preference chosen.